Development of a novel spiral antenna system for low loop voltage current start-up at the Steady State Superconducting Tokamak (SST-1). (26th November 2021) - Basu, Debjyoti; Raju, Daniel; Singh, Raj; Mukherjee, Aparajita; Patel, Manoj; Rathi, Dharmendra; Trivedi, R G; Vasava, Kirit; Jadeja, K A; Jayaswal, Sneha P; Patel, Vijaykumar N; Patnaik, S K; et al.
Abstract: In general, superconducting tokamaks require low loop voltage current start-up for the safety purpose of their poloidal field coils. The loop voltage inside the vacuum vessel of Steady State Superconducting Tokamak (SST-1) is low in nature since its central solenoid is located outside the cryostat. The low loop voltage current start-up of the SST-1 is routinely performed by using the electron cyclotron resonance (ECR) method at the toroidal magnetic field B t = 1.5 T (first harmonic) and 0.75 T (second harmonic). Recently, an alternative RF-based plasma current start-up system has been planned for operating the machine, especially for a higher toroidal magnetic field regime 1.5 T ⩽ B t ⩽ 3 T . The system was already developed based on an antenna system, made of a series of combinations of two flat spiral antennas, to assist plasma current start-up at a lower inductive electric field. It has already been tested and installed in the SST-1 chamber. The system testing was performed without a background magnetic field within the frequency regime of 35 MHz–60 MHz at present. The test results show that it can produce an electron density of n e ≃ 10 16 m − 3 measured by the Langmuir probe at the expense of 500 W RF power. The spectroscopy results indicate its capability of producing plasma density greater than 10 13 m − 3 and an electron temperature of T e = 2 –6 eV. In addition, the results also show the presence of a turbulent electric field of the order of 10 6 V m −1 at the antenna center and a finite anomalous temperature of neutral particles. Calculations show that the obtained density is sufficient for SST-1 low loop voltage plasma breakdown. The antenna system is also capable of producing plasma at higher frequencies. This article will discuss the development of the prototype and the installed antenna system along with their test results in detail.